Charles Taylor, Freeman Dyson, John Polkinghorne, John Barrow, Ian Barbour, Holmes Rolston, Martin Rees - Shirley, Clifford, photographer (Colorado State University. Libraries, 2012)
Photograph featuring Dr. Rolston and other Templeton laureates. Left to right: Charles Taylor (2007 laureate, Catholic philosopher, McGill University, Canada), Freeman Dyson (2000 laureate, physicist, Princeton University), John Polkinghorne (2002 laureate, physicist and Anglican priest, Cambridge University), John Barrow (2006 laureate, cosmologist, mathematician, Cambridge University), Ian Barbour (1999 laureate, physicist, Carleton College), Holmes Rolston (2003 laureate, philosopher, Colorado State University),and Martin Rees (2011 laureate, astrophysics, cosmology, Cambridge University).
Keywords: Templeton laureates; Colorado State University; philosophy professor; Templeton Prize; Rolston, Holmes, 1932-2025